2020
DOI: 10.3348/kjr.2020.0037
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Treatment for Benign Parathyroid Lesions: Treatment Efficacy and Safety Based on Nodule Characteristics

Abstract: This study aimed to evaluate the efficacy and safety of ultrasound (US)-guided minimally invasive treatment in patients with parathyroid lesions. Materials and Methods: This study included 27 patients who had undergone US-guided radiofrequency ablation (RFA) or ethanol ablation (EA) for parathyroid lesions between January 2010 and 2018. RFA was performed in 19 patients with primary hyperparathyroidism (PHPT, n = 11) or secondary hyperparathyroidism (SHPT, n = 8), and EA was performed in eight patients with sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 33 publications
(67 reference statements)
4
35
0
Order By: Relevance
“…Partial remission of hyperparathyroidism caused by incomplete ablation had also been reported in previous studies [10,20]. Based on the three patients with operative failure due to incomplete ablation in the present study, our recommendations are summarized as follows: (i) a complete ablation should contain both hypoechoic hyperplastic nodules and normal parathyroid tissue, which often appear hyperechoic on US, especially after the injection of the isolation solution (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Partial remission of hyperparathyroidism caused by incomplete ablation had also been reported in previous studies [10,20]. Based on the three patients with operative failure due to incomplete ablation in the present study, our recommendations are summarized as follows: (i) a complete ablation should contain both hypoechoic hyperplastic nodules and normal parathyroid tissue, which often appear hyperechoic on US, especially after the injection of the isolation solution (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…20 Twelve patients had decreases in the serum calcium and iPTH levels after RFA, and 19 had complete normalization of the serum calcium and iPTH levels. 5,15,16 Only 3 patients had minor complications. RFA in all the cases was performed under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Nine reports were identified that described 32 cases of PHPT treated with RFA (Table ). 5,[14][15][16][17][18][19][20][21] In these cases, RFA was performed because of either contraindication to surgery or the patient refusing surgery, and there was limited follow-up. Of note, in 1 case, RFA was performed inadvertently when a parathyroid adenoma was mistaken for a thyroid nodule; this was the only case where there was no improvement in biochemical profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I recently read the article titled “Minimally invasive treatment for benign parathyroid lesions: treatment efficacy and safety based on nodule characteristics” with great interest [ 1 ]. The authors performed radiofrequency ablation (RFA) for primary hyperparathyroidism (PHPT) and secondary hyperparathyroidism (SHPT), which are solid lesions of the parathyroid glands.…”
mentioning
confidence: 99%